Cassia fistula leaves; UHPLC-QTOF-MS/MS based metabolite profiling and molecular docking insights to explore bioactives role towards inhibition of pancreatic lipase - Ul Aabideen, Zain; Mumtaz, Muhammad Waseem; Akhtar, Muhammad Tayyab; Raza, Muhammad Asam; Mukhtar, Hamid; Irfan, Ahmad; Raza, Syed Ali; Touqeer, Tooba; Nadeem, Muhammad; Saari, Nazamid (Multidisciplinary Digital Publishing Institute, 2021)
The present work was aimed at investigating hydroethanolic leaf extracts of Cassia fistula for their antioxidant and pancreatic lipase (PL) enzyme inhibitory properties. The most active extract was selected to profile the phytoconstituents by UHPLC-QTOF-MS/MS technique. Among the tested extracts, the 80% hydroethanolic extract exhibited the maximum levels of total phenolic and flavonoid contents (TPC and TFC) with a contribution of 201.3 ± 2.6 mg of gallic acid equivalent per gram of extract (GAE/g extract), and 116.3 ± 2.4 mg of rutin equivalent per gram of extract (RE/g extract), respectively. The same extract also showed promising 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and PL inhibitory activity with an IC50 (half maximal inhibitory concentration) of 30.5 ± 2.8 µg/mL and 17.31 ± 1.18 μg/mL, respectively. The phytochemical profiling of 80% hydroethanolic extract confirmed the presence of 23 metabolites of immense medicinal significance. Docking studies were conducted to investigate the potential interactions of compounds identified in the study. The docking study-based binding energy data and the interaction scheme both revealed the possible role of the identified compounds towards PL inhibitor. Moreover, energies of frontier molecular orbitals (FMOs), ionization potentials (IP), electron affinities (EA) and molecular electrostatic potentials (MEP) were also explored. The findings of the current work suggest that C. fistula is a promising natural source of antioxidant and antiobesity agents, which may be exploited to add pharmacological functionalities to food.